2013
DOI: 10.7314/apjcp.2013.14.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and Behavior of Malaysia Undergraduate Female Students in a Public University Toward Breast Self-examination Practice

Abstract: Background: Breast cancer is the most common cancer and the second principal cause of cancer deaths among women worldwide, including Malaysia. Methods: A cross-sectional study was carried out among 262 female undergraduate students in University Putra Malaysia using a validated questionnaire which was developed for this study. Results: The mean age of respondents was 22±2.3 years. Most of them were single (83.1%), Malay (42.3%) and 20.7% reported having a family history of breast cancer. Eighty-seven (36.7%) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
42
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 20 publications
7
42
1
1
Order By: Relevance
“…In contrast to our finding, there are some studies indicate that there are no significant relationship between having a family member diagnosed with BC or other cancer type and BSE performance (Gucuk and Uyeturk, 2013). Another study supported this lack of significant association between family history of breast cancer, and BSE practices were carried out among Malaysian undergraduate female students in a public university (Akhtari-Zavare et al, 2013). Having family members diagnosed with breast diseases could have empowered participants' awareness about BSE performance and increased sensitiveness towards the risk development of BC.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our finding, there are some studies indicate that there are no significant relationship between having a family member diagnosed with BC or other cancer type and BSE performance (Gucuk and Uyeturk, 2013). Another study supported this lack of significant association between family history of breast cancer, and BSE practices were carried out among Malaysian undergraduate female students in a public university (Akhtari-Zavare et al, 2013). Having family members diagnosed with breast diseases could have empowered participants' awareness about BSE performance and increased sensitiveness towards the risk development of BC.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, majority of participants (97%) reported that they had hear about breast cancer but only 26% of them performed BSE. These findings are support by Akhtari-Zavare et al (2013) that reported 97% of the participants heard about BSE, only 36.7% stated that they performed BSE and among those who practice BSE, most of them practice BSE occasionally (50, 57.5%). Similarly, in a study from Turkey reported less than half of the respondents participated BSE and a few are doing BSE regularly (Andsoy and Gul, 2014).…”
Section: Discussionsupporting
confidence: 79%
“…Similar to the finding of this study, Alsaif (2004) has reported that the majority of nursing students had performed BSE. In the previous studies it has reported that the incidence rate of female students performed BSE is low (Akhtari-Zavare et al, 2013;Al-Sharbatti et al, 2013;Che et al, 2014). Taking into consideration the fact that various factors play a role in urging individuals to have performed BSE like cultural beliefs, perception of health-disease, support of the family and social environment, belief in the importance of the applications which are required for early diagnosis of the disease (Nahcivan and Secginli, 2003;Cam and Gumus, 2006) we are pleased to see that the nursing students who are the subjects of this study had a high rate of having BSE done since this reflect that they have a high level of awareness.…”
Section: Discussionmentioning
confidence: 99%